2020
DOI: 10.3390/rs12111859
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spring–Neap Tidal Cycle on Spatial and Temporal Variability of Satellite Chlorophyll-A in a Macrotidal Embayment, Ariake Sea, Japan

Abstract: We investigated the spatio-temporal variability of chlorophyll-a (Chl-a) and total suspended matter (TSM) associated with spring–neap tidal cycles in the Ariake Sea, Japan. Our study relied on significantly improved, regionally-tuned datasets derived from the ocean color sensor Moderate Resolution Imaging Spectroradiometer (MODIS) Aqua over a 16-year period (2002–2017). The results revealed that spring–neap tidal variations in Chl-a and TSM within this macrotidal embayment (the Ariake Sea) are clearly differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Similarly, the total suspended sediment (TSM), which is a major constituent in coastal waters, is involved in processes such as light attenuation, pollutant propagation, and waterway blockages. The spatial distribution of TSM is an indicator of deposition and erosion patterns in estuaries and coastal zones and a necessary input deposition and erosion patterns in estuaries and coastal zones and a necessary input for estimating the material fluxes from the land through rivers to the sea [1][2][3][4][5]. However, satellite ocean color datasets are fraught with missing data caused by improper conditions, such as clouds and rain [3,6].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, the total suspended sediment (TSM), which is a major constituent in coastal waters, is involved in processes such as light attenuation, pollutant propagation, and waterway blockages. The spatial distribution of TSM is an indicator of deposition and erosion patterns in estuaries and coastal zones and a necessary input deposition and erosion patterns in estuaries and coastal zones and a necessary input for estimating the material fluxes from the land through rivers to the sea [1][2][3][4][5]. However, satellite ocean color datasets are fraught with missing data caused by improper conditions, such as clouds and rain [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Chl-a and TSM are two common indicators of water quality. There have been several efforts to estimate the spatial and temporal variability of Chl-a and TSM in the Ariake Sea using satellite ocean color data [1,18]. Using significantly improved, regionally-tuned Moderate Resolution Imaging Spectroradiometer (MODIS) datasets from 2002 to 2017, Yang et al [1] reported that the Chl-a variability during the spring-neap tidal cycle in the region off Saga (Figure 1) was generally controlled by TSM in seasons other than summer, Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations